2022
DOI: 10.1142/s1088424622300014
|View full text |Cite
|
Sign up to set email alerts
|

Development of controlled reactions using an element-based design of azaporphyrinoid materials

Abstract: Phthalocyanines (Pcs) and related macrocycles (azaporphyrinoids) are well-known artificial dyes in modern material chemistry. Several strategies for fine-tuning their optical/electrochemical/aromatic properties have been proposed. The diversity of Pcs enables novel functionalities that can assist in innovative approaches to tune and improve the properties of diverse material. Organic synthesis yields a wide array of organic molecules. Herein, the author describes two methods for developing controlled reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Recently, with the increasing interest in red light-induced reactions, more applications of porphyrinoids in this field are disclosed. [32][33][34][35][36]40 In 2021, the Furuyama group demonstrated that Ru phthalocyanine (RuPc) 5e could also act as a competent PC (Scheme 5d). 32 Under the red light, the treatment of alkenes 33 with trifluoromethanesulfonyl chloride 60 in the presence of 5e and K 2 HPO 4 furnished trifluoromethylethyl chlorides 61 in 44-91% yields.…”
Section: Porphyrinoids and Azaporphyrinoidsmentioning
confidence: 99%
“…Recently, with the increasing interest in red light-induced reactions, more applications of porphyrinoids in this field are disclosed. [32][33][34][35][36]40 In 2021, the Furuyama group demonstrated that Ru phthalocyanine (RuPc) 5e could also act as a competent PC (Scheme 5d). 32 Under the red light, the treatment of alkenes 33 with trifluoromethanesulfonyl chloride 60 in the presence of 5e and K 2 HPO 4 furnished trifluoromethylethyl chlorides 61 in 44-91% yields.…”
Section: Porphyrinoids and Azaporphyrinoidsmentioning
confidence: 99%
“…[27][28][29][30][31] However, controlling the reactivity of the phthalonitriles on the basis of the different electronic characteristics of the substituents that can modify the involved electrophilicity/nucleophilicity is underdeveloped. 32 One of the outstanding strategies to prepare Pcs with certain chemo-and regiocontrol is the use of bisphthalonitriles linked by constrained binding groups. [16][17][18][19][20] In particular, the introduction of optically active binaphthyl units as bridges deserves special mention since they lead to optically active Pcs thanks to the intrinsic atropisomerism of the binaphthol subunit.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In these systems, the controlled photoexcited state of phthalocyanines is realized through precise modifications of the phthalocyanine structure. 7 Their high rigidity and large molar absorption coefficient are anticipated to enable long-duration operation with a minimal catalyst loading. Thus, longer-wavelength-light-mediated re- actions facilitated by phthalocyanine catalysts can be expected to unveil novel synthetic pathways, particularly the direct modification of visible-light-absorbing materials, tandem reactions with shorter-wavelength-light-mediated reactions, 8 and under shielded conditions such as those in cell reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Red-to-near-infrared light (600–900 nm), which encompasses a substantial proportion of solar energy, holds promise for selective reactions of diverse substrates and environments due to the limited number of interacting substances in this wavelength region. Nevertheless, the development of catalysts tailored for the appropriate use of this lower-energy light poses considerable challenges and constitutes a nascent area of research in the field of organic synthesis. , A notable contribution from our group in this context was the pioneering development of reactions catalyzed by red-to-near-infrared-activatable phthalocyanine catalysts. , In these systems, the controlled photoexcited state of phthalocyanines is realized through precise modifications of the phthalocyanine structure . Their high rigidity and large molar absorption coefficient are anticipated to enable long-duration operation with a minimal catalyst loading.…”
Section: Introductionmentioning
confidence: 99%